Physicochemical and metabolite profiling of three Capsicum species from West Sumatra, Indonesia - RINA YENRINA; WELIARDI WELIARDI; ARIF RIZKIKA PUTRA; SITI SARAH HUMAIRA; TUTY ANGGRAINI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Yenrina R, Weliardi, Putra AR, Humaira SS, Anggraini T. 2026. Physicochemical and metabolite profiling of three Capsicum species from West Sumatra, Indonesia. Biodiversitas 27 (4): d270405. https://doi.org/10.13057/biodiv/d270405. Fresh chili quality and bioactivity vary by species and growing conditions, but integrated data for West Sumatra remain limited. This study provides the first integrated physicochemical-metabolite characterization of three Capsicum species commonly cultivated and marketed in the region: Red Curly chili (Capsicum annuum; RC), Bird's Eye chili (Capsicum frutescens; BE), and Ghost Pepper (Capsicum chinense; GP). Fruit morphometrics, surface color (CIELAB), proximate composition, and antioxidant activity (DPPH assay at 1000 ppm) were evaluated using a descriptive analytical approach, and metabolite profiling was performed using untargeted LC-MS/MS QTOF with putative identification based on MS/MS spectral library matching (MSI level 2). These three species exhibit distinct morphological and color parameters, with RC exhibiting the highest red intensity (a* and chroma) and BE the lowest lightness (L*). All samples exhibited high moisture content (78.70-82.46%) and high carbohydrate content, with low fat and protein levels. Strong antioxidant activity was detected across species (83.38-86.67%). Untargeted LC-MS/MS analysis of single composite samples per species identified 147 putative metabolites (MSI level 2) (73 in RC, 78 in BE, and 70 in GP), and qualitative differences in metabolite detection patterns were observed among species. Glycosylated terpenoid-related compounds were detected in BE, abietic-type diterpenoids were detected in GP, and RC showed the presence of apocarotenoid-related compounds such as β-ionone together with diverse diterpenoid annotations. As analyses were based on single composite samples and putative metabolite annotation (MSI level 2), results should be interpreted as qualitative trends rather than statistically validated differences. Overall, this study establishes a region-specific integrated physicochemical-metabolite profile of Capsicum species from West Sumatra, providing a structured reference for future quantitative metabolomics, functional evaluation, and cultivar differentiation.